2018
DOI: 10.1108/sbr-08-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Money laundering through gambling devices

Abstract: Purpose The aim of this paper is to examine how money laundering occurs through electronic gaming devices, the regulatory requirements for operators of electronic gaming machines, the issues of on-line versus land-based gambling and a discussion about ethics and social responsibility. Design/methodology/approach This is primarily a conceptual paper which includes an identification of several theories relevant to money laundering. Primary data were obtained from one respondent through a face-to-face meeting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Foley et al ( 2019 ), for example, show the significant amount of illegal activities related to the use of cryptocurrencies, a problem that gambling regulators know as well (Potenza et al, 2000 ; Spapens, 2014 ; Albanese, 2018 ). Especially when it comes to money laundering, both markets face significant challenges (Wechsler, 2001 ; Levi and Reuter, 2006 ; Buchanan, 2018 ). Recent research has shown that people are now putting their money into cryptocurrencies, thereby replacing their usual risk-taking preferences from CFD-trading (Pelster et al, 2019 ), stock market day-trading and sports betting (Delfabbro et al, 2021 ).…”
Section: Examples For the Different Approaches To Gambling And Financ...mentioning
confidence: 99%
“…Foley et al ( 2019 ), for example, show the significant amount of illegal activities related to the use of cryptocurrencies, a problem that gambling regulators know as well (Potenza et al, 2000 ; Spapens, 2014 ; Albanese, 2018 ). Especially when it comes to money laundering, both markets face significant challenges (Wechsler, 2001 ; Levi and Reuter, 2006 ; Buchanan, 2018 ). Recent research has shown that people are now putting their money into cryptocurrencies, thereby replacing their usual risk-taking preferences from CFD-trading (Pelster et al, 2019 ), stock market day-trading and sports betting (Delfabbro et al, 2021 ).…”
Section: Examples For the Different Approaches To Gambling And Financ...mentioning
confidence: 99%
“…Corporate money laundering/gambling activities have garnered increased attention from government, citizenry and the media. For example, a Royal Commission into the financial services industry has recently exposed malpractices in Australia (Buchanan, 2018; Royal Commission into Misconduct in the Banking, Superannuation and Financial Services Industry, 2019). The final report and the Government’s response are available on the Department of Treasury website (The Australian Government, The Treasury, 2019).…”
Section: Introductionmentioning
confidence: 99%